Water management consideration in the Lubin-Głogów Cupriferous Basin = Uwarunkowania wodne eksploatacji miedzi w Lubińsko-Głogowskim Okręgu Miedziowym - Kołodziejczyk, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Lubin-Głogów Cupriferous Basin is an area of intensive mining exploitation. The four active underground copper mines are: "Lubin", "Polkowice", "Sieroszowice" and "Rudna". In work are characterised topical states of hydrogeological conditions and are showed the directions of further protecting activities against hydrogeological degradation of this region.
Keywords: miedź; eksploatacja zasobów naturalnych; Lubińsko-Głogowski Okręg Miedziowy (LGOM); cooper; natural resources exploitation; drainage; water management